A Guide to Quantitative Biomarker Assay Development using Whispering Gallery Mode Biosensors. Issue 3 (14th September 2017) - Robison, Heather M.; Bailey, Ryan C.
Abstract : Whispering gallery mode (WGM) sensors are a class of powerful analytical techniques defined by the measurement of changes in the local refractive index at or near the sensor surface. When functionalized with target‐specific capture agents, analyte binding can be measured with very low limits of detection. There are many geometric manifestations of WGM sensors, with chip‐integrated silicon photonic devices first commercialized because of the robust, wafer‐scale device fabrication, facile optical interrogation, and amenability to the creation of multiplexed sensor arrays. Using these arrays, a number of biomolecular targets have been detected in both label‐free and label‐enhanced assay formats. For example, sub‐picomolar detection limits for multiple cytokines were achieved using an enzymatically enhanced sandwich immunoassay that showed high analyte specificity suitable for detection in complex, clinical matrices. This protocol describes a generalizable approach for the development of quantitative, multiplexed immunoassays using silicon photonic microrings as an example WGM platform. © 2017 by John Wiley & Sons, Inc.